Scanf-CD (Science chromatography art and design fiction on filter paper-Chromdeco) - Kamal, Nurul Syahadah; Aripin, Muhammad Amirullah; Zainol, Zuhairie; Ab Sah, Mohammad Johaiwisah; Julaihi @ Basri, Jemat (2022)
Chromatography techniques are based on including column, thin layer, and paper chromatography. They are not only associated with scientific experiments but also become artworks. In this innovation project, filter paper is used because it has high solvent absorption. It is used to ensure the accuracy of the motifs produced and will be dried in a certain period to produce an interesting combination of art colours and fictional designs. The main objective of the ScanF- CD (Science Chromatography Art and Design Fiction on Filter Paper -ChromDeco) innovation project is to highlight the results of art and design fiction motifs, which are produced through chromatography techniques using filter paper. The novelty is divided into three, first, the results of chromatography between the absorption and separation of the pigments to colour will combine two types of solutes, namely mobilizing agent and colour agents. Next, the resulting motifs are then taken digitally to be composed using Picasa computer software. Lastly, the end product will be produced using art and fiction design of filter paper chromatography, which are; hanging decoration, bookmark, stationery cup, wall decoration, and picture frame on the market. Permanent agent is used in 12.5cm ashless filter paper brand double rings. Colour agent is used as a soluble material that can be purchased in the market. In conclusion, we have learned a lot from this project, for example, the chromatography techniques by using filter paper to produce some art and design fiction motifs.